Supervisi Dalam Pendidikan Islam - Renny Mayasari (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Supervision has a basic concept that is interrelated with education or commonly called supervision. In the basic concepts of supervision of basic education some are about the concept of supervision. While the process of supervising is a series of compilation of supervision carried out and the efforts made by supervisors in seeing and fostering the whole process of implementing education. In its development, the supervision of education gives good to the development of special education in Indonesia, especially Islamic education so that the level of professionalism of teachers in teaching is done well, both in madrasas and religious education teachers in schools. Therefore, supervision is needed in the education process based on two important things. First, curriculum development which is the progress of education. These developments often occur changes in structure and function of the curriculum. Therefore, the implementation of an approved curriculum is continuous with real conditions in the field. Second, the development of personnel, employees, or employees is always a continuing effort in an organization.2 This journal discusses the nature of Islamic education supervision, the urgency of Islamic education supervision, the objectives and principles of Islamic education supervision, and the supervision and change of Islamic education.